Ruthenium Complexes in the Fight against Pathogenic Microorganisms. An Extensive Review - Alexandra-Cristina Munteanu; Valentina Uivarosi (MDPI AG, 2021)
The widespread use of antibiotics has resulted in the emergence of drug-resistant populations of microorganisms. Clearly, one can see the need to develop new, more effective, antimicrobial agents that go beyond the explored 'chemical space'. In this regard, their unique modes of action (e.g., reactive oxygen species (ROS) generation, redox activation, ligand exchange, depletion of substrates involved in vital cellular processes) render metal complexes as promising drug candidates. Several Ru (II/III) complexes have been included in, or are currently undergoing, clinical trials as anticancer agents. Based on the in-depth knowledge of their chemical properties and biological behavior, the interest in developing new ruthenium compounds as antibiotic, antifungal, antiparasitic, or antiviral drugs has risen. This review will discuss the advantages and disadvantages of Ru (II/III) frameworks as antimicrobial agents. Some aspects regarding the relationship between their chemical structure and mechanism of action, cellular localization, and/or metabolism of the ruthenium complexes in bacterial and eukaryotic cells are discussed as well. Regarding the antiviral activity, in light of current events related to the Covid-19 pandemic, the Ru (II/III) compounds used against SARS-CoV-2 (e.g., BOLD-100) are also reviewed herein.